Circuit training: 2 - Reynolds, F.
For athletes, the general preparation period before the beginning of actual competitions is an ideal time to initiate a resistance training programme. A four- to eight-week period of sound resistance training helps to develop a nice foundation of suppleness (mobility), strength, and stamina (endurance), to which athletes can add speed and racing skill just before the competitive season begins. 'Circuit training' is an excellent way to simultaneously build strength and stamina.